High-Throughput Imaging for the Discovery of Cellular Mechanisms of Disease. Issue 9 (September 2017) - Pegoraro, Gianluca; Misteli, Tom
Abstract : High-throughput imaging (HTI) is a powerful tool in the discovery of cellular disease mechanisms. While traditional approaches to identify disease pathways often rely on knowledge of the causative genetic defect, HTI-based screens offer an unbiased discovery approach based on any morphological or functional defects of disease cells or tissues. In this review, we provide an overview of the use of HTI for the study of human disease mechanisms. We discuss key technical aspects of HTI and highlight representative examples of its practical applications for the discovery of molecular mechanisms of disease, focusing on infectious diseases and host–pathogen interactions, cancer, and rare genetic diseases. We also present some of the current challenges and possible solutions offered by novel cell culture systems and genome engineering approaches. Trends: HTI is a powerful method in basic research, drug discovery, and identification of disease mechanisms. HTI uses automated microcopy and image analysis to extract numerical cellular features that can be used to measure cellular pathways activity and/or morphological phenotypes. HTI assays can be used to screen and profile large collections of perturbing reagents (compounds, RNAi, CRISPR/Cas9), or to precisely quantify rare biological events. Since HTI assays can be adapted to study a wide variety of cellular phenotypes, this technique has been adopted to identify cellular pathways and genes altered in pathogen infection, cancer, and monogenic diseases, among others. HTI has utility in chemical screens to discover novel cancer vulnerabilities for potential pharmacological intervention.